Linguatula serrata in the anterior chamber of the eye - Muna Bhende; Abhishek; Jyotirmoy Biswas; M Raman; Pramod S Bhende (Indian Journal of Ophthalmology, 2014)
We report a case of intraocular Linguatula in healthy young female who presented with a history of trivial trauma, dislocated lens, inflammation and secondary glaucoma. A mobile worm was seen in the anterior chamber. Pars plana lensectomy and vitrectomy was planned to remove both the cataractous lens and the parasite during which the worm disappeared from view but was later recovered from the cassette fluid. It was identified as the nymphal form of Linguatula serrata (tongue worm).